Clinical Risk Factors for Cutaneous Squamous Cell Carcinoma in Patients with Actinic Keratosis or Cutaneous Squamous Cell Carcinoma in Situ: A Retrospective Double-cohort Study - Knuutila, Jaakko S.; Kaijala, Olli; Lehto, Salla; Vahlberg, Tero; Nissinen, Liisa; Kähäri, Veli-Matti; Riihilä, Pilvi (Medical Journals Sweden AB, 2025)
Actinic keratosis and cutaneous squamous cell carcinoma in situ are precancerous forms of cutaneous squamous cell carcinoma. In this single-centre retrospective study, patients with histopathologically confirmed actinic keratosis (n=121) or cutaneous squamous cell carcinoma in situ (n=99) as their initial keratinocyte-derived lesion were compared and evaluated with regard to development of cutaneous squamous cell carcinoma during a 5-year observation period. Patients with severely dysplastic actinic keratosis or cutaneous squamous cell carcinoma in situ as their initial lesion developed cutaneous squamous cell carcinoma more rapidly than patients with actinic keratosis with mild or moderate dysplasia. With either actinic keratosis or cutaneous squamous cell carcinoma in situ as an initial lesion, advanced age, male sex, comorbidity with basal cell carcinoma, and immunosuppressive medication were associated with elevated risk of cutaneous squamous cell carcinoma development. Regarding solely patient with actinic keratosis as their initial lesion male sex, advanced age, immunosuppressive medication, location of the initial lesion, and degree of dysplasia were associated with the risk of cutaneous squamous cell carcinoma. Among patients with cutaneous squamous cell carcinoma in situ as their initial lesion, only aspirin usage was associated with increased risk of cutaneous squamous cell carcinoma. This study indicates that, among the vast and increasing population of patients with cutaneous squamous cell carcinoma precursors, male patients with immunosuppressive medication who develop basal cell carcinoma should be regarded as at heightened risk of cutaneous squamous cell carcinoma development and warrant closer surveillance.